A Herschel and BIMA study of the sequential star formation near the W 48A H ii region. Issue 1 (11th March 2014) - Rygl, K. L. J.; Goedhart, S.; Polychroni, D.; Wyrowski, F.; Motte, F.; Elia, D.; Nguyen-Luong, Q.; Didelon, P.; Pestalozzi, M.; Benedettini, M.; Molinari, S.; André, Ph.; et al.
Abstract: We present the results of Herschel HOBYS ( Herschel imaging survey of OB Young Stellar objects) photometric mapping combined with Berkeley Illinois Maryland Association (BIMA) observations and additional archival data, and perform an in-depth study of the evolutionary phases of the star-forming clumps in W 48A and their surroundings. Age estimates for the compact sources were derived from bolometric luminosities and envelope masses, which were obtained from the dust continuum emission, and agree within an order of magnitude with age estimates from molecular line and radio data. The clumps in W 48A are linearly aligned by age (east-old to west-young): we find a ultra-compact (UC) H ii region, a young stellar object (YSO) with class II methanol maser emission, a YSO with a massive outflow and finally the NH2 D prestellar cores from Pillai et al. This remarkable positioning reflects the (star) formation history of the region. We find that it is unlikely that the star formation in the W 48A molecular cloud was triggered by the UC H ii region and discuss the Aquila supershell expansion as a major influence on the evolution of W 48A. We conclude that the combination of Herschel continuum data with interferometric molecular line and radio continuum data is important to derive trustworthy age estimates and interpret the origin of large-scale structures through kinematic information.